ER stress and slit diaphragms: is there a connection? - Hermle, Tobias Franz; Simons, Matias (Kidney international, 2023)
Galloway-Mowat syndrome is a neurorenal syndrome that has been linked with defective transfer RNA and protein translation caused by variants in the multiprotein complex KEOPS. In the kidney, this syndrome seems to primarily affect the podocytes, but the pathogenesis has remained unclear. In this issue of Kidney International, Krausel et al. use Drosophila nephrocytes to link endoplasmic reticulum stress with defects in the slit diaphragm.
Gesehen am 12.06.2023